Na medida certa? O Princípio da Intervenção Precoce e suas repercussões no processo de ruptura com o ato infracional - LEITE, Lisandra Nazaré Roma Assunção (2023)
This work deals with the problem of state intervention with adolescents who commit their first infractions in São Luís. It emphasizes aspects of the historical construction of the protection policy for children and adolescents in Brazil, with special attention to those related to adolescents in conflict with the law and juvenile justice. Preventive and socio-educational policies are studied based on their complexity and the historical, cultural and economic determinations that surround them. For the construction of the dissertation, bibliographical research was carried out in secondary sources, documental research on service data in various instances of the socio- educational system and basic social policies, and complementary questionnaires were applied to managers and specialists. It is concluded that intervention with adolescents does not occur quickly enough and that the current system is not very effective in preventing the negative evolution of adolescents in the practice of the infraction.